Neuraxial analgesia effects on labour progression: facts, fallacies, uncertainties and the future. (4th August 2014) - Grant, EN; Tao, W; Craig, M; McIntire, D; Leveno, K
<x xml:space="preserve">Abstract</x> Approximately 60% of women who labour in the USA receive some form of neuraxial analgesia, but concerns have been raised regarding whether it negatively impacts the labour and delivery process. In this review, we attempt to clarify what has been established as truths, falsities and uncertainties regarding the effects of this form of pain relief on labour progression, negative and/or positive. Additionally, although the term 'epidural' has become synonymous with neuraxial analgesia, we discuss two other techniques, combined spinal‐epidural and continuous spinal analgesia, that are gaining popularity, as well as their effects on labour progression.